2022
DOI: 10.3389/fmed.2022.869976
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profile in Aqueous Humor of Patients With Ocular Toxocariasis

Abstract: PurposeOcular toxocariasis (OT) is a vision-threatening disease with a largely unknown intraocular pathogenesis. Herein, we determined the cytokine expression profile in aqueous humor (AH) of patients with OT.MethodsThis is a retrospective case-control study of cytokine levels in AH of patients with OT and uveitis and control subjects. Thirty samples from eyes with OT, 23 from eyes with non-OT uveitis, and 25 from eyes with age-related cataract were analyzed using a multiplexed magnetic bead immunoassay. Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A previous study found increased levels of IL-10 in the lungs on post-infection days 7 and 14 [ 17 ], whereas another study observed elevation of IL-10 in the peripheral blood 14 days post-infection [ 7 ]. Jiang et al [ 18 ] have reported a significant increase in the expression of aqueous humor IL-10 in human ocular toxocariasis. Here, IL-10 elevation was not observed in BAL fluid even 5 weeks after infection, indicating that the expression of regulatory cytokines may vary depending on the infection site [ 7 ], and the duration of expression may differ for each cytokine.…”
mentioning
confidence: 99%
“…A previous study found increased levels of IL-10 in the lungs on post-infection days 7 and 14 [ 17 ], whereas another study observed elevation of IL-10 in the peripheral blood 14 days post-infection [ 7 ]. Jiang et al [ 18 ] have reported a significant increase in the expression of aqueous humor IL-10 in human ocular toxocariasis. Here, IL-10 elevation was not observed in BAL fluid even 5 weeks after infection, indicating that the expression of regulatory cytokines may vary depending on the infection site [ 7 ], and the duration of expression may differ for each cytokine.…”
mentioning
confidence: 99%